The May 25th 2011 railroad embankment failure in Ann Arbor, Michigan, as a means for teaching geotechnical engineering - Zekkos, Dimitrios; Athanasopoulos-Zekkos, Adda; Grizi, Athena; Greenwood, William (International Society for Soil Mechanics and Geotechnical Engineering, 2016)
A 30-m long railroad embankment failure that occurred on May 25 2011 in the city of Ann Arbor, Michigan, is presented. Emphasis is given on the field observations of the failure, the characterization of the site conditions and the seepage and slope stability analyses, all of which represent important components of the training and practice of a geotechnical engineer. The failure occurred following a record wet season that resulted in ponding water against the embankment and high enough water pressures and exit gradients that resulted in instability of the railroad embankment. Detailed background material and the methodology for using the case history in geotechnical engineering education are presented.